Infrared Antireflective and Protective Coatings - Zhu, Jiaqi; Han, Jiecai (De Gruyter, 2018)
This book is a comprehensive introduction on infrared anti-transparent materials and their applications in anti-reflective and protective coatings. Optical, mechanical and thermal properties and preparations of various kinds of films, such as amorphous diamond films, germanium carbide films, boron phosphide films, alumina films and yttrium oxide film are discussed in detail making it suitable for material scientists and industrial engineers.